Postura craniocervical, disfunção temporomandibular e cervical em pacientes com apneia obstrutiva do sono - Piccin, Chaiane Facco (2015)
This research aimed to investigate the presence and severity of temporomandibular (TMD) and cervical dysfunction, craniofacial features and craniocervical posture in patients with obstructive sleep apnea (OSA) compared to healthy subjects and to determine possible relationship of cephalometric and photogrammetry variables with the severity of OSA. This study was a case-control and evaluated 21 subjects with OSA, who were the obstructive apnea group of sleep (GOSA) and 21 healthy subjects, who were the control group (GC). The subjects of the GOSA were diagnosed by baseline polysomnography of all night. It was used, respectively, the inventory Diagnostic Criteria for Temporomandibular Disorders Research Axes I and II and Temporomandibular Index, to assess the presence and severity of TMD. To evaluate the presence of craniocervical dysfunction, it was used the Craniocervical Dysfunction Índex. Cephalometry was used for evaluation of craniofacial measures, head posture and air space measures. Head posture was also evaluated by means of photogrammetry. It used the statistical software Statistica version 9.1. The distribution of the data was assessed by the Shapiro-Wilk normality test. For data comparison with normal distribution, we used the Student t test unpaired or the Mann-Whitney U test in cases of non-normality. The Chi-square or Fisher's exact was used to assess associations between categorical variables. The correlations between variables were assessed using Pearson's correlation coefficient (quantitative variables) or Spearman (quantitative or qualitative ordinal variables).The groups were homogeneous in relation to sex (12 men and 9 women in each group), age (GOSA = 41.86 ± 11.26 years; GC = 41.19 ± 11.20 years), Body Mass Index (BMI) (GOSA = 25.65 ± 2.46 kg/m2; GC = 24.72 ± 3.01 kg/m2). GOSA presented greater occurrence of cervical symptoms than GC (62% versus 33%, respectively), with more severity (p=0.040) also in this group. For the presence and severity of signs and symptoms of TMD, 57.14% of the subjects with GOSA were diagnosed with TMD, against 28.57% in the control group, but this difference was not significant (p = 0.061; p = 0.349). The severity of TMD between the groups was similar, both in moderate degree. The GOSA had a lower average pharyngeal space and greater distance between the hyoid bone and the mandibular plane in GOSA when compared to the CG (p = 0.037; p = 0.005). There was a correlation between higher hyperextension of the head, evaluated by photogrammetry and cephalometric, and most forward head as assessed by cephalometry, with the greatest severity of OSA assessed by the Apnea/Hypopnea Index (AHI). This study found that both groups had mild cervical dysfunction, but had significantly higher scores in the group with OSA. Patients with OSA were more likely to TMD, decreased pharyngeal airway and increasing distance from the hyoid bone to mandibular plane, suggesting the influence of craniofacial changes in OSA. In addition, the increased severity of OSA recorded by AHI correlated with higher hyperextension and forward head.